Sleep quality among engineering students at UNIMAS - Wong Xin, Zi (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to investigate the sleep quality among the engineering students at UNIMAS. The study identified the relationship between and sleep quality and academic achievement (CGPA) of engineering students and also examined the influence of demographic factors (gender and year of study) on sleep quality. A quantitative correlation research and questionnaire of Pittsburgh Sleep Quality Index (PSQI) is adopted and used as instrument to collect data. Stratified random sampling is used to obtain the balance respondents in this study. The findings of this study have showed that there is strong positive relationship between sleep quality and academic achievement (r = 0.680, p=0.000). There is also significant difference of sleep quality based on gender (t =7.083, p=0.000). The findings indicated that there is a weak negative correlation between sleep quality and year of study of engineering students (r = -0.442, p=0.000). There are also various perception and opinion from the respondents on the sleep quality and most of them agree that sleep quality give impact on academic achievement.